Screening examination of speech as a means of identyfing children at risk of speech disorders - Szurek, Mateusz (Selected issues from the theory and practice of speech therapy, 2018)
Screening diagnosis of speech helps single out children from the risk group of the appearance of the speech impediments and taking the speech-therapy early intervention towards them. The current speech-therapy care at the pre-schools is embracing only children with statements about the need of the special education, however recent research data is showing high level of speech defects in pre-school children and the majority from them isn’t provided with specialist therapy at the pre-school. The screening is contributing to the reduction in the number of children with the speech impediments thanks to more accurate further diagnostics and therapeutic action. Detecting the defect at a young age is precipitating therapy and is helping in building the correct speech system. The screening prevention of speech defects allows additionally to notice other developmental abnormalities which can become apparent in the course of conducted examinations. The aim of the article is to show the scale of the problem of undiagnosed speech defects and to emphasize the importance of early diagnose of said defects. The research results allowed to show the current scale of speech defects appearance in one of the pre-schools in Lodz Voivodeship.